1987
DOI: 10.4102/abc.v17i2.1036
|View full text |Cite
|
Sign up to set email alerts
|

Leaf anatomy of the genus <i>Ehrharta</i> (Poaceae) in southern Africa: the Villosa group

Abstract: The leaf blade anatomy of Ehrharta villosa Schult. f. var. villosa, var. maxima Stapf and E. thunbergii Gibbs Russell is described and illustrated. These three taxa, constituting the Villosa species group, share a diagnostic leaf anatomy distinguished by the absence of a distinct midrib, adaxial semi-radiate mesophyll with the abaxial chloren-chyma palisade-like in arrangement, rectangular long cells and the stomatal apertures which are overlapped by four cuticular flanges projecting from the two adjacent inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Microscopic examinations of Turakina Beach specimens of pypgrass by Hodder (1997) have confirmed that plants are the same as those described by Ellis (1987). Pypgrass is a C3 plant, so does not have the physiological advantages of C4 plants with respect to efficient use of water.…”
Section: Introductionmentioning
confidence: 53%
“…Microscopic examinations of Turakina Beach specimens of pypgrass by Hodder (1997) have confirmed that plants are the same as those described by Ellis (1987). Pypgrass is a C3 plant, so does not have the physiological advantages of C4 plants with respect to efficient use of water.…”
Section: Introductionmentioning
confidence: 53%
“…E. villosa var. villosa, which is concentrated geographically in the middle part of the distribution of the group, also has morphological and anatomical (Ellis 1987b) interm ediates to both the other taxa. The rhizome differences between the species may be related to habitat differences.…”
Section: Resultsmentioning
confidence: 99%
“…Morphologically, the Villosa group is linked to the Calycina group by the hairy spikelets with long glumes, and to the C a pensis group by the large spikelets with short-awned or m ucronate and stipitate sterile lemmas, and by the 'bulbous' internodes. Ellis (1987b) identified as E. villosa and 10 as E. thunbergii ( = E. gigantea) but considered as a single species. This paper describes and illustrates the leaf blade anatom y of the taxa of the Villosa group and dis cusses the affinities of these taxa and of the species group by reference to this anatomical evidence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations